Beam splitter entangler for nonlinear Bosonic fields - Ooi, Chong Heng Raymond; Abdel-Khalek, S.; Berrada, K. (IOP Publishing, 2012)
Some years ago Katriel and Solomon [1] described applications to the characterization of the photon statistics of nonideal lasers, nonclassical light, and deformed photon states using f-deformed coherent states. In this letter, we study the effect of a beam splitter on these nonlinear coherent states. We find that these states are useful for generating quantum entanglement as the deformation parameter gets farther form the unity and for strong input field regimes. The results are confirmed through the Werhl entropy.